PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUASAN KONSUMEN MIE GC JEMBER - Lestari, Dwi Ayu; Mayasari, Fariza Kurnia; Khusniah, Khasin; Safira, Imelda Khairiza; Rumsiyah, Silatur; Qomariah, Nurul (Fakultas Ekonomi dan Bisnis, 2025)
Mie GC, as one of the popular instant noodle brands in Indonesia, faces the challenge of understanding how these two factors contribute to purchasing decisions and customer satisfaction. One of the main players in this market is Mie GC which has succeeded in attracting consumer interest with various flavor variants and product innovations. Product quality covers various aspects, including taste, texture, packaging, and nutritional value. The aim of this research is to determine the influence of product quality and price variables on consumer satisfaction at